The context of irrigation development: Overview - Desai, Gunvant M. (International Food Policy Research Institute, 1990)
Professor Vaidyanathan's chapter focuses on major issues emerging from the past experience of irrigation development. These include (1) the choice between large and small irrigation works, (2) delays in construction, (3) underuti 1 ization of the created potential, (4) quality of irrigation, (5) means of achieving qualitative improvement, (6) productivity impact of irrigation, (7) pricing of irrigation water, (8) equity aspects of irrigation development, and (9) environmental concerns. Thus, his canvas covers issues that touch on practically every stage from the planning and execution of irrigation projects to their ultimate impact.